The Quest For A Uniform Multimodal Regime: Persevere, Abandon Or Start Again? - Dunster, Rennard (Department of Commercial Law, 2014)
This thesis provides a short background to multimodal transport and an overview of the problems currently facing the industry. The accepted models for a solution are considered and an analysis is then conducted of the strengths and weaknesses of the two recent attempts at producing a uniform legal regime for multimodal transport namely; the Draft Instrument and The United Nations Convention On International Multimodal Transport Of Goods, 1980 ("the Multimodal Convention"). As neither of these attempts appear to be a tenable solution, I then examine whether the quest for uniformity should be abandoned or, if the process were to begin again, what lessons can be learned from the failures of these attempts.